PENGARUH EVENT SERVICE QUALITY, EVENT PRICE DAN EVENT VENUE TERHADAP EVENT SATISFACTION DALAM PENYELENGGARAAN ASIAN GAMES 2018 DI KOTA PALEMBANG - Dwi Intan Sari; Isnurhadi Isnurhadi; Esa Sukmawijaya; Marlina Widiyanti (UNIB Press, 2020)
This study aims to determine the effect of event service quality, event price and event venue on event satisfaction of event Asian Games 2018 in Palembang. The data used in this study are primary data by distributing questionnaire to 100 respondents who was watching Asian Games 2018 in Palembang. The analysis technique used is multiple linear regression analysis. Based on the results of this studies using SPSS versi 23 demonstrated that: (1) Event service quality has a positive and significant effect on event satisfaction at Asian Games 2018 in Palembang. 2) Event price don’t has a positive and not significant effect on event satisfaction at events Asian Games 2018 in Palembang (3) Event service venue has a positive and significant effect on event satisfaction at events Asian Games 2018 in Palembang. Percentage value of determination coefficient of 58,3%. This means that 58,3% of the effect of event satisfaction can be explained from the three independent variables. While remaining 41,7% is explained by other variables not examined in this study.